Primary hyperparathyroidism: Dynamic postoperative metabolic changes. (1st October 2017) - Kaderli, Reto M.; Riss, Philipp; Geroldinger, Angelika; Selberherr, Andreas; Scheuba, Christian; Niederle, Bruno
Summary: Objective: Little is known about the natural changes in parathyroid function after successful parathyroid surgery for primary hyperparathyroidism. The association of intact parathyroid hormone (iPTH) and calcium (Ca) with "temporary hypoparathyroidism" and "hungry bone syndrome" (HBS) was evaluated. Design: Potential risk factors for temporary hypoparathyroidism and HBS were evaluated by taking blood samples before surgery, intra‐operatively, at postoperative day (POD) 1, at POD 5 to 7, in postoperative week (POW) 8 and in postoperative month (POM) 6. Patients: Of 425 patients, 43 (10.1%) had temporary hypoparathyroidism and 36 (8.5%) had HBS. Measurements: The discriminative ability of iPTH and Ca on POD 1 for temporary hypoparathyroidism and HBS. Results: Intact parathyroid hormone (IPTH) on POD 1 showed the highest discriminative ability for temporary hypoparathyroidism (C‐index = 0.952), but not for HBS. IPTH was helpful in diagnosing HBS between POD 5 and 7 (C‐index = 0.708). Extending the model by including Ca resulted in little improvement of the discriminative ability for temporary hypoparathyroidism (C‐index = 0.964) and a decreased discriminative ability for HBS (C‐index = 0.705). Normal parathyroid metabolism was documented in 139 (32.7%) patients on POD 1 and in 423 (99.5%) 6 months postoperatively, while 2 (0.5%) patients had persistent hyperparathyroidism, one diagnosed between POD 5 and 7 and another at POW 8. No patients suffered from permanent hypoparathyroidism. Conclusions: The necessity for Ca and vitamin D3 substitution cannot be predicted with certainty before POD 5 to 7 without serial laboratory measurements. Based on the results, a routine 8‐week course of Ca and vitamin D3 treatment seems reasonable and its necessity should be evaluated in a follow‐up study.